Answers

2014-08-06T04:49:41+08:00
1. First, we expand the expression: ((4^2)(y^4) / (x^6))^1/2 --> By laws of exponents, we multiply 1/2 by the exponents of the terms: [(4^2/2)(y^4/2) / (x^6/2)] = (4y^2 / x^3) 2. We first expand the expression: [(2^3) / (x^3)(y^9)]^2/3 --> By laws of exponents, we multiply thte exponenets of the terms by 2/3: [(2^6/3) / (x^6/3)(y^18/3)] = (4 / x^2 y^6) 3. Since there are no fraction exponents, we now proceed into multiplying the exponents: [((-2)^4)(a^12/2) / (b^4)] = (16a^6 / b^4) 4. Since there is an operation, we first expand the term: (a^1/2 - b^1/2)(a^1/2 - b^1/2) = (a^2/2 - 2(a^1/2)(b^1/2) + b^2/2) = a - 2(a^1/2)(b^1/2) + b
0
2014-08-06T08:24:46+08:00